DETERMINATION OF METHAMPHETAMINE IN URINE SAMPLES BY GC-MS METHOD USING SOLID PHASE EXTRACTION (SPE) - Đoàn, Đặng Văn; Huy, Đỗ Quang; Huệ, Nguyễn Đức; Trí, Trần Mạnh (Vietnam Journal of Science and Technology, 2012)
SUMMARY This paper reports on the study for determination of Methamphetamine in urine samples by GC-MS method using Solid Phase Extraction (SPE). The aim of the study was investigation on the GC-MS method for determination of Methamphetamine in urine samples. The method is based on the extraction of Methamphetamine by usingof Solid Phase Extraction technique with C18 and its determination by GC-MS. The method was then successfully applied for the determination of Methamphetamine in real samples.